الثقافة الرقمية : دراسة تحليلية في المفهوم Digital Culture: An Analytical Study in Concept - محمدي صليحة; بخوش سامي (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
ساهم استخدام الواسع للتكنولوجيا الالكترونية الجديدة في إيجاد أساليب جديدة لأنماط حياة جديدة بعد أفول الثقافات التقليدية، وصعود و بلورة معطيات ثقافية جديدة أصبح يطلق عليها الثقافة الرقمية، خاصة وأن ثقافة الجيل الجديد بلغت من التعقيد إلى أن أصبحت متعددة المشارب والمفاهيم، ومتفرعة إلى أطر تحكمها عوالم افتراضية، بفعل تكنولوجيا الاتصالات الرقمية تحت مسمى صناعة الثقافة، ومن ثم تعرضت الثقافة في هذا العصر إلى تغير فانقلبت مظاهر القيم الجمعية إلى قيم فردية مع ظهور ثقافة الشباب المتأثر بأنظمة الثقافة التقنية السريعة التدفق نتيجة تنامي استخدام التكنولوجيا ووسائل الاتصال الحديثة من قبل الاجيال الجديدة، حتى بات العالم قرية صغيرة تنتشر فيه المعرفة بسرعة قياسية، وصارت فيه الممارسات الثقافية مرتبطة بالفضاء الرقمي مخللة مجموعة من القواعد، وهو ما يدل على حدوث تحولات شاملة للثقافة في هذا العصر الرقمي وأن العالم يشهد تزايد أهمية الثقافة الرقمية. The widespread use of new electronic technology has contributed to finding new ways of new lifestyles after the demise of traditional cultures, and the emergence and crystallization of new cultural data that has become called digital culture, especially since the culture of the new generation has reached a complexity that has become multi-line and conceptual, and branched into frameworks governed by virtual worlds, And manifestations of collective values turned into individual values with the emergence of the youth culture influenced by the fast-flowing technical culture systems as a result of the increasing use of technology and modern means of communication by new generations, and cultural practices have become linked to the digital space, BRIC Ki a set of rules that indicate the occurrence of comprehensive cultural transformations in this digital age and that the world is witnessing the increasing importance of digital culture.